1991
DOI: 10.1093/ajcn/53.5.1185
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of the n − 3 eicosapentaenoic and docosahexaenoic acids as ethyl esters and triglycerides by humans

Abstract: Five normolipemic subjects received three test meals containing 28 g n-3 (omega-3) fatty acids provided as 1) triglycerides, 2) ethyl esters, and 3) ethyl esters + 12 g olive oil. The control meal contained olive oil. When equivalent amounts of fat were given, the increase in chylomicron and plasma triglycerides was similar; n-3 fatty acid contents were also similar after n-3 fatty acid intake as ethyl esters or triglycerides. Ethyl esters alone were well absorbed and produced similar n-3 fatty acid responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 21 publications
5
73
0
1
Order By: Relevance
“…On one hand, the supply of dietary n-3 PUFA in the form of ethyl esters does not impair the intestinal absorption of these fatty acids. 13 On the other hand, the intestinal absorption does not differ between n-3 fatty acids and other fatty acids. 26 Accordingly, the higher gross food ef®ciency in the groups fed high-fat diets might result from the fact that the energy cost of lipid deposition from dietary lipids (5% of the energy potential of lipids) is considerably lower than that from dietary carbohydrate (25% of the energy potential of carbohydrate).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, the supply of dietary n-3 PUFA in the form of ethyl esters does not impair the intestinal absorption of these fatty acids. 13 On the other hand, the intestinal absorption does not differ between n-3 fatty acids and other fatty acids. 26 Accordingly, the higher gross food ef®ciency in the groups fed high-fat diets might result from the fact that the energy cost of lipid deposition from dietary lipids (5% of the energy potential of lipids) is considerably lower than that from dietary carbohydrate (25% of the energy potential of carbohydrate).…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl esters of fatty acids do not impair the bioavailability of the fatty acids. 12,13 The fatty acid composition of the diets (Table 1) was determined by gas±liquid chromatography using a CP9000 gas chromatograph (Chrompak, Les Ulis, France) ®tted with an AT-WAX fused-silica capillary column (60 m 6 0.25 mm, Alltech Templeuve, France).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…12) On the other hand, Nordoy et al found no difference in either EPA or DHA incorporation, regardless of the formulation. 13) Previous studies showed that dietary 1,3-diacylglycerol (DG), but not TG with similar fatty acid composition, reduced body fat accumulation, 14,15) and that dietary DG, which was prepared from rapeseed fatty acids and mainly composed of 1,3-DG, reduced the serum level of TG in rats compared with TG of rapeseed oil. 16) However, there is little information available about the effects of DHA supplemented in the form of DG.…”
mentioning
confidence: 99%
“…Oral administration of omega-3 EE to healthy volunteers [40][41][42] and hypertriglyceridemic subjects 42 is followed by EPA and DHA absorption. After a first complete hydrolysis of omega-3 EE, EPA and DHA are absorbed and incorporated into plasma phospholipids and cholesterol esters, as reported in animal studies.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%